The impacts of precision livestock farming tools on the greenhouse gas emissions of an average Scottish dairy farm - Ferguson, H. J.; Bowen, J. M.; McNicol, L. C.; Bell, J.; Duthie, C-A.; Dewhurst, R. J. (Frontiers in Sustainable Food Systems, 2024)
Precision livestock farming (PLF) tools are increasingly used in daily herd management to improve health, welfare, and overall production. Whilst not intended to reduce greenhouse gas (GHG) emissions on farm, PLF tools can do so indirectly by improving overall efficiency, thereby reducing the emissions per unit of product. This work modelled the potential effects of commercially available PLF tools on whole enterprise and product emissions of two average Scottish dairy farm systems (an 8,000L and 10,000L herd) using the Agrecalc carbon footprinting tool. Scenarios modelled included an improvement in fertility and an improvement in fertility and yield from the introduction of an accelerometer-based sensor, and an improvement in health from introduction of an accelerometerbased sensor, with and without the use of management interventions. Use of a sensor intended to improve fertility had the largest reduction in total emissions (kg CO2e) of -1.42% for a 10,000L farm, with management changes applied. The largest reduction in emissions from milk production (kg CO2e) of -2.31% was observed via fertility technology application in an 8000L farm, without management changes. The largest reduction in kg CO2e per kg fat and protein corrected milk of -6.72% was observed from an improvement in fertility and yield in a 10,000L herd, with management changes. This study has highlighted the realistic opportunities available to dairy farmers in low and high input dairy systems to reduce their emissions through adoption of animal mounted PLF technologies.